2012
DOI: 10.1029/2011jd017385
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between El Niño and the western North Pacific summer climate in a coupled GCM: Role of the transition of El Niño decaying phases

Abstract: [1] This study investigates the impacts of the transition of El Niño decaying phases on the western North Pacific anticyclone (WNPAC) anomalies in the subsequent summer with a coupled GCM. The modeling results suggest that the El Niños with short decaying phases lead to significant WNPAC anomalies in the following summer, which are contributed to mainly by the El Niños followed by La Niñas, in comparison with those not followed by La Niñas. In contrast, the long decaying cases are associated with the disappear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 49 publications
(60 reference statements)
1
34
0
Order By: Relevance
“…For example, a strong La Niña event developed in 1998 summer (with Niño3.4 SST at −1.2 • C) following a record El Niño. Such variability in the SST gradient between the IO and tropical Pacific contributes to the TNW Pacific AAC (Terao and Kubota, 2005;Chen et al, 2012;Cao et al, 2013;Xiang et al, 2013). Recent studies have also suggested a contribution from the tropical Atlantic (Rong et al, 2010;Hong et al, 2014;Chen et al, 2015;Yu et al, 2015).…”
Section: Sst Forcingmentioning
confidence: 98%
“…For example, a strong La Niña event developed in 1998 summer (with Niño3.4 SST at −1.2 • C) following a record El Niño. Such variability in the SST gradient between the IO and tropical Pacific contributes to the TNW Pacific AAC (Terao and Kubota, 2005;Chen et al, 2012;Cao et al, 2013;Xiang et al, 2013). Recent studies have also suggested a contribution from the tropical Atlantic (Rong et al, 2010;Hong et al, 2014;Chen et al, 2015;Yu et al, 2015).…”
Section: Sst Forcingmentioning
confidence: 98%
“…However, Chen et al (2012Chen et al ( , 2016 argued that the El Niño events with fast decaying phases could lead to significant stronger WPSA in the subsequent summer. Such discrepancy is partly attributed to the different definition of fast decaying El Niño, and partly due to the different analysing period between Chen et al's and our work.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The cold SST anomaly over the equatorial Pacific is also in favor of an enhanced WNPSH via stimulating anticyclonic Rossby wave to its northwest Xiang et al 2013). Therefore, it is recognized that the increased zonal SST gradient between a warm TIO and a cold tropical Pacific Ocean enhances the WNPSH (Terao and Kubota 2005;Chen et al 2012;Cao et al 2013). The WNPSH can also be enhanced by the descending branch of the enhanced local Hadley circulation induced by the warm SST anomaly over the Maritime Continent (Sui et al 2007;Wu and Zhou 2008;Chung et al 2011) or enhanced by anticyclonic Rossby wave generated by local cold SST anomaly over the WNP (Wang et al 2000;Wu et al 2010;Wang et al 2013).…”
Section: Introductionmentioning
confidence: 95%